The Effect of Slow Deep Breathing Therapy on Reducing Blood Pressure in Hypertension Patients in Luwihaji Village Based on Nola J. Pender's Theory - Erlinda Fera Salsabila; Novia Dwi Astuti; Ahmad Maftuhin; Siti Patonah (International Journal of Health Engineering and Technology, 2026)
Hypertension is a major non-communicable disease in Luwihaji Village due to limited access to health care and low knowledge of non-pharmacological therapy. This study aims to examine the effect of slow deep breathing therapy on lowering blood pressure based on Nola J. Pender's Health Promotion Model theory. Using a quasi-experimental pretest-posttest design with a control group, a population of 40 hypertension sufferers was sampled with 30 respondents (15 intervention, 15 control) via simple random sampling. The digital sphygmomanometer instrument was analyzed univariately (frequency, mean) and bivariately (Paired T-Test, α=0.05) using SPSS. The results showed a significant decrease in systolic blood pressure (161.40 to 151.73 mmHg) and diastolic blood pressure (99.07 to 94.20 mmHg) in the intervention group (p=0.000), 100% of respondents decreased versus stable controls (p=0.082). It was concluded that slow deep breathing therapy was effective in lowering blood pressure significantly.